Performance of Plant Seed Supervisors at BPSB Central Java - Muhammad Tafakur Azhim; Istiatin; Sarsono (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to determine the influence simultaneously (simultaneously) and partially of the variables of competence, independence, motivation, and use of information technology on the performance of plant seed supervisors at BPSB Central Java. This research method uses a quantitative research design. The population of all plant seed supervisors working at BPSB Central Java is 83 employees. The sampling technique used in this research was a census technique with a sample size of 83 employees. Data collection using questionnaires. The data analysis techniques used for statistical analysis are multiple linear regression test, F test, t test, and coefficient of determination. The research results show that competence, independence, motivation, and the use of information technology partially and significantly influence the performance of plant seed supervisors at BPSB Central Java. Suggestions from this research, BPSB Central Java continues to improve competence, independence, motivation and use of existing information technology, so that the performance of plant seed supervisors will increase and be better than before.